Documentation Management Based on ISO for Construction Industries in Developing Countries - Senaratne, Sepani; Mayuran, Jeevana (Penerbit Universiti Sains Malaysia, 2015)
Improper document management (DM) can produce poor and erroneous documents and cause major issues, such as claims and disputes, in construction projects. Adopting a proper documentation management system (DMS) will enable the smooth completion of construction projects to overcome such issues. Quality management systems such as the International Standard Organisation (ISO) standards are designed with generic DM requirements. In developed countries, standard project management procedures and manuals are often used to guide such document requirements. However, construction industries in developing countries are still behind in this regard. Hence, this study aimed to explore the current DM requirements in the Sri Lankan construction industry and the reasons for poor DM and provides suggestions for overcoming these problems. A questionnaire was given to a sample of 30 large construction-contracting organisations operating in Sri Lanka, all of which had ISO certification. The findings revealed 40 DM-related construction activities and their needs and uses by the selected companies. Based on the suggestions given by respondents, this study proposes how to implement these activities and develop an appropriate DMS for the construction industry. This research will offer useful implications for developing countries that use similar standards and encounter similar DM issues.